Entrepreneurial management technology for nursing professionals - Dirce Stein Backes; Marcelo Junior Toson; Léris Salete Bonfati Haeffner; Mara Teixeira Caino Marchiori; Regina Gema Santini Costenaro (Revista Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to validate entrepreneurial management technology for the nursing practice. Methods: methodological study, carried out based on the development of an entrepreneurial management technology, based on literature review and, later, content validation by 11 experts, recognized by their peers as entrepreneurs. The validation process took place through Delphi conferences, between June and September 2018. Results: on the second round of Delphi conferences, at least 90% agreement was obtained on all items. In addition, all items were validated as pertinent and considered prospective and inducing of new thinking and acting among nursing professionals who wish to undertake and explore opportunities, goods, and services in the area. Final Considerations: it was noted that the experts, in general, showed good adherence to the initiative and ease in validating the theoretical-conceptual dimension and the dimension of “Personal/professional qualities necessary for the performance of entrepreneurial management”; however, they had difficulty in validating the methodological steps.